Gluten-free diet and quality of life in celiac disease - Samasca, Gabriel (Shaheed Beheshti University of Medical Sciences, 2014)
Many recent studies overshadow the effects of gluten-free diet. Gluten-free diet positive effects were observed in celiac disease patients: increase in body mass index, higher energy intakes, reducing adiposity gain, moderates the risk of the associated complications. However, adhering to a gluten-free diet is difficult for many people. A new solution is needed for quality of life of celiac disease patients, not for celiac disease treatment. Health education on gluten-free diet at home and in society seems to be the solution. The aim of our study is to evaluate the recent research on gluten-free diet as a nutritional therapy for patients with celiac disease. To achieve this purpose we have analyzed the published studies from 2008 to the present on nutrition in celiac disease.